Uma Leitura Crítica de O Deus das Pequenas Coisas: as memórias de Rahel - Belem, Eleide Moreira Araújo (2021)
The aim of this work is to study the representation of the national identity and some aspects of Indian culture in the novel The God of Small Things (1998) by Arundhati Roy through an analysis that focuses on the how the author deconstructs and criticizes the representation of Indian cultural identity still based on the caste system to which is attributed the stratification of Indian society. The discussion also takes into account in what the novel portrays the cultural changes that took place in Indian society as a result of its contact with Western culture, in particular through the English colonization of the subcontinent.